SOME ASPECTS OF CURRENT STATE OF FINANCING THE HOTEL BUSINESS IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
A number of scientific researches related to the field have been studied in researching some aspects of current state of financing the hotel business in Uzbekistan. Equity capital and structure of liabilities of hotels operating in the Republic of Uzbekistan, key aspects of financing the hotel business at Agrobank JSCB and others are analyzed. Conclusions and proposals are developed based on the conducted research.